2005
DOI: 10.1080/10428190500054350
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the age-adjusted International Prognostic Index in chemosensitive recurrent or refractory non-Hodgkin's lymphomas treated with high-dose BEAM therapy and autologous stem cell transplantation

Abstract: High-dose therapy (HDT) is now recommended for patients under 60 years of age with chemosensitive relapsed aggressive non-Hodgkin's lymphoma. However, approximately half of these patients will be cured by HDT. Prognostic factors are needed to predict which patients with chemosensitive lymphoma to second-line therapy could benefit from HDT. We retrospectively investigated the prognostic value of the widely used age-adjusted International Prognostic Index (AA-IPI) calculated at the time of relapse (35 patients) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
1
9
1
Order By: Relevance
“…An adaptation of the IPI, the age-adjusted IPI (aa-IPI, excludes age and extent of extra nodal disease) has been proposed as a better prognostic system in patients undergoing transplantation, reflecting the uniformly young population included in early series. Although aa-IPI at relapse did not predict the outcome of patients undergoing transplantation in the Parma trial, 15 this finding conflicts with subsequent series where IPI-R 16,17 or aa-IPI 18,19 were able to predict survival after transplantation. These series, although very informative, included multiple histologies of lymphoma, broad variety of conditioning regimens (some using TBI), heterogeneous source of stem cells and often restricted inclusion to younger patients.…”
Section: Transplantation; Beam Regimencontrasting
confidence: 55%
See 1 more Smart Citation
“…An adaptation of the IPI, the age-adjusted IPI (aa-IPI, excludes age and extent of extra nodal disease) has been proposed as a better prognostic system in patients undergoing transplantation, reflecting the uniformly young population included in early series. Although aa-IPI at relapse did not predict the outcome of patients undergoing transplantation in the Parma trial, 15 this finding conflicts with subsequent series where IPI-R 16,17 or aa-IPI 18,19 were able to predict survival after transplantation. These series, although very informative, included multiple histologies of lymphoma, broad variety of conditioning regimens (some using TBI), heterogeneous source of stem cells and often restricted inclusion to younger patients.…”
Section: Transplantation; Beam Regimencontrasting
confidence: 55%
“…16 The same institution later reported 98 patients with refractory or relapsed chemosensitive DLBCL (including 'transformed' cases) undergoing autologous SCT and identified aa-IPI at the time of initiation of second-line chemotherapy as a predictor of OS and DFS at 4 years. 19 Jabbour et al 18 in a series of 40 patients with aggressive NHL undergoing autologous transplantation also identified aa-IPI as being a predictor of OS and DFS. This study, however, found that TTR did not predict outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The IPI and its variants are the primary prognostic tools used in patients with DLBCL. In the pre-rituximab era, when the aaIPI was applied to patients with chemosensitive recurrent or refractory aggressive non-Hodgkin's lymphomas who had been treated with high-dose therapy followed by Auto-SCT, the scores were predictive of OS ( P =0.034) [14]. A recent prospective study reported a 2-year PFS and OS of 63% and 73%, respectively, in aaIPI high-intermediate- and high-risk patients with aggressive B-cell lymphoma who had been treated with R-CHOP alone [5].…”
Section: Discussionmentioning
confidence: 99%
“…The International Prognostic Index (IPI) calculated at the time of relapse (IPI-R) or the age-adjusted IPI have also been used. Although the ageadjusted IPI did not influence the outcome in the Parma trial [26], in subsequent studies both the IPI-R and the ageadjusted IPI predicted survival after ASCT [27,28]. Costa et al [29] showed that IPI-R and the time from initial diagnosis to relapse (TTR) both influenced outcomes after ASCT for relapsed, chemosensitive disease.…”
Section: Prognostic Factors Of Asctmentioning
confidence: 99%
“…Markers of poor prognosis at relapse include older age, advanced stage, chemorefractory disease, short remission duration, and the presence of significant comorbidities [26,28,69]. Outcome after recurrence is poor, with a median survival of less than 12 months [69].…”
Section: Allogeneic Transplantationmentioning
confidence: 99%